1995
DOI: 10.1177/1357633x9500100406
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Rural Areas. Experience with Medical Desktop-Conferencing via Satellite

Abstract: Cooperation between physicians in hospitals in rural areas can be assisted by desktop-conferencing using a satellite link. For six weeks, medical desktop-conferencing was tested during daily clinical conferences between the Virchow-Klinikum, Berlin, and the Medical Academy, Wroclaw. The communications link was provided by the German Telekom satellite system MCS, which allowed temporary connections to be established on demand by manual dialling. Standard hardware and software were used for videoconferencing, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…3 The peer-review process is obvious for the paper addressing telemedicine in Poland published in 1995. 6 The number of articles published per year fluctuated from 0 to 16, with an overall increasing trend (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The peer-review process is obvious for the paper addressing telemedicine in Poland published in 1995. 6 The number of articles published per year fluctuated from 0 to 16, with an overall increasing trend (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis revealed that video conferences and imaging data transmission via satellite between Polish and German clinicians from departments of radiology in Berlin and Wrocław opened the new age of telemedicine implementations in Poland in 1995. 6 Since then, the Internet and other telecommunications-based systems have become important sources of health-related information that have started to supplement conventional health services across Europe. 7,8 Research conducted in Poland and other countries clearly shows that the interest in telemedicine is growing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the field of telemedicine is both broadly defined and applied, as well as having fluid borders with tele-education and health-on-the-go, further sources were found in this search that do not fall under the broader categories discussed above [310,312,313,319,320,323,324,328,329,[333][334][335]338,339,341,342,344,[347][348][349][350]354,357,358,360,362,363,365,369,370,375,377,379,380,382,385,388,389,412,391,392,394,452,395,398].…”
Section: Insights From the Literature Reviewmentioning
confidence: 99%
“…Recent technical developments are image transmission protocols that allow the ability to alter the window and level settings of radiological images (e. g. CT and MR images) over the Internet while maintaining short transmission times [7,19,24,45,50]. Thus, teleradiology/telemedicine will be a powerful tool in optimizing diagnosis as well as in providing accurate treatment and patient care.…”
Section: Applications In Radiologymentioning
confidence: 99%